PERBEDAAN IMUNOEKSPRESI CD10 DAN MMP9 ANTARA HIPERPLASIA ENDOMETRIUM TIPE ATIPIK DAN KARSINOMA ENDOMETRIOID YANG BERDIFERENSIASI BAIK (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Background: Endometrial hyperplasia is one of the malignancy triggers for endometrium. Based on histopathologic features, it is divided into two types: atypical and non-atypical. Endometrial carcinoma is one of the gynecological malignancies, ranked 5th the world for its malignancy. Endometrial carcinoma is divided into two types, type I (endometrioid), and type II (non endometrioid). In histopathology, particularly in the sample of tissue curettage process, It is difficult to distinguish between endometrial hyperplasia atypical and well-differentiated endometrioid carcinoma. CD10 plays a role for homeostasis in extracellular matrix (ECM). If there is regulation disruption, it can lead to carcinogenesis. Whilst, MMP9 plays its role in the occurrence of invasion and metastasis. The aim of this study is to investigate the immunoexpression differences of CD10 and MMP9 in atypical endometrial hyperplasia and well-differentiated endometrioid carcinoma. So, this study can be used to determine a more accurate diagnosis especially on the tissue curettage sample. Methods: This study is an observational study by using cross sectional design. Total sample was 52 cases from hysterectomy which are consist of 26 cases atypical endometrial hyperplasia and 26 cases well-differentiated endometrioid carcinoma. Those samples and cases were obtained from the Department of Anatomical Pathology in three hospitals in Bandung: Hasan Sadikin, Advent and Santosa. Therefore, the whole samples were marked by immunohistochemical CD10 and MMP9. Results: The results of this study found a statistically, significant differences between immunoexpression of CD10 and MMP9 with atypic endometrial hyperplasia and well-differentiated endometrioid carcinomas. The p values for CD10 and MMP9 are 0.003 and 0.008, respectively. Atypical endometrial hyperplasia and well-differentiated endometrioid carcinomas are significantly influenced by CD10 and MMP9, CD10 immunoexpression is the most influential variable. Conclusion: Based on the results of this study it can be concluded that Immunoxpression of CD10 and MMP9 can be used as an immunohistochemical marker to differentiate atypical endometrial hyperplasia from well-differentiated endometrioid carcinoma, particularly on tissue curettage sample. Keywords: CD10, MMP9, endometrial hyperplasia atypic type, well-differentiated endometrioid carcinoma.